2013
DOI: 10.5539/gjhs.v6n2p138
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors on Hypertensive Disorders among Jordanian Pregnant Women

Abstract: Eight percent of pregnancies involve hypertensive disorders, which can have serious complications for mothers and children. There has only been minimal research into hypertension in pregnancy in developing countries, including Jordan. Therefore, this study aimed to identify how frequent certain risk factors that apply to hypertensive disorders during pregnancy were among women in the Jordanian capital of Amman. A prospective case-control study was conducted on 184 Jordanian pregnant patients with hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
5
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
6
5
1
1
Order By: Relevance
“…Unlike several studies which reported diabetic women were at an increased risk of developing HDP [56,61], our review did not find this association. It is possible that we did not obtain similar results because of the small number of studies that were included in this meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike several studies which reported diabetic women were at an increased risk of developing HDP [56,61], our review did not find this association. It is possible that we did not obtain similar results because of the small number of studies that were included in this meta-analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we found a significantly higher risk of developing HDP occurred in women who had a low educational level. In agreement with this, studies conducted in various countries reported low educational level put women at a higher risk of developing HDP [61,62]. Women in SSA countries are mostly uneducated and may not understand how important early identification of associated factors and early initiation of ANC visits are.…”
Section: Discussionmentioning
confidence: 64%
“…First of all, the knowledge of the negative effect of diabetes mellitus on HDP has been widely accepted, which is the most common risk factor in published reports 2,7,15,16 . Similarly, family history of hypertension was also a predictor in the multivariate analysis, which was consistent with most of the previous literature 6,17,18 .…”
Section: Discussionsupporting
confidence: 84%
“…Gestational diabetes mellitus was also found to be an independent predictor of hypertensive disorders of pregnancy that supported the existing knowledge; because literatures noted that pregnant mother who developed diabetes mellitus would have higher predisposition to develop hypertensive disorders of pregnancy and it has been identified as the most common predictor in previous studies [22, 34, 3638]. …”
Section: Discussionsupporting
confidence: 77%